STRATEGI ADOPSI SOFTWARE SISTEM INFORMASI BARU: STUDI TERHADAP IMPLEMENTASI RMS - Syarifuddin Syarifuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The advancement of information technology has an influence on the organization when the technology is adopted. Information technology can affect the nature and effectiveness of communication processing, coordination and control within the organization. Some mindset developers of information systems tend to focus on analysis and development not on implementation. Though the success or failure of information systems software project depends on the success of implementation and value obtained by the client. Errors in implementation may lead to failure to adopt information technology. Problems related to the planning and implementation of information technology should be taken seriously by management. To improve the success of the adoption of an information system, it is necessary for a system implementer to implement an implementation strategy supported by communication skill to support the success of system implementation. Appropriate application and implementation of technology can enable the technology to become a strategic property. The use of information technology as a strategic asset in organizing and managing organizations can make organizations more responsive, flexible and efficient or even organizations can excel in competing.